Teknologi Modifikasi Fisik Heat Moisture Treatment (HMT) pada Tepung Beras dan Tepung Sorgum: Kajian Sistematis Parameter Proses, Transformasi Struktur Granula Pati dan Prospek Skalabilitas Industri - Puji Hastuti, Ririn; Alel, Ariya Eka; Alfarisi, Cory Dian; Legawati, Lisa; Aziz, Yelmida (SURYA TEKNIKA, 2026)
Heat Moisture Treatment (HMT) is a clean-label, residue-free physical starch modification technique that serves as a strategic solution for food diversification, aiming to reduce national reliance on imported wheat, which reached USD 2.2 billion in 2022. This systematic review of 45 selected scientific publications, out of 65 initially screened articles, evaluates the impact of HMT on rice and sorghum flour characteristics. Synthesized results indicate that HMT consistently increases gelatinization temperature (To up by 3 - 8°C), reduces peak viscosity (15 - 30%), and boosts resistant starch content from 3 - 5% to 8 - 15%. In sorghum flour, the interaction between starch and non-starch components, particularly kafirin proteins, significantly modifies the HMT response compared to pure sorghum starch. This study highlights critical research gaps, specifically regarding the need for optimal HMT parameters tailored to Indonesian local varieties and the necessity of comprehensive techno-economic analysis to facilitate industrial-scale implementation.